Criminal Law Policy in the Eradication of Narcotics Crimes in the Belawan Port Area - H.Habeahan, Abdul Ryfay; Kusbianto, Kusbianto; Maysarah, Andi (STAINI Press, 2026)
Narcotics crimes constitute serious and transnational forms of organized crime, in which port areas represent highly vulnerable entry points for illicit drug trafficking. Belawan Port, as a strategically important international port in Indonesia, has significant potential to be exploited as a gateway for the smuggling and distribution of illegal narcotics. This study aims to analyze the regulation of criminal law policy in combating narcotics crimes in port areas, examine the implementation of criminal law policy in the Belawan Port region, and identify the obstacles encountered in its enforcement. The research employs a normative juridical method, utilizing statutory and conceptual approaches supported by secondary legal materials. The findings indicate that criminal law policies related to narcotics control have been comprehensively regulated; however, their implementation at Belawan Port has not been fully effective due to structural, substantive, and cultural constraints. Therefore, strengthening inter-agency coordination among law enforcement authorities and adopting a more integrated approach combining penal and non-penal measures are necessary to enhance the effectiveness of narcotics crime prevention and eradication in port areas.